Circadian rhythm and day to day variability of serum potassium concentration: a pilot study - Schmidt, Stefan; Ditting, T.; Deutsch, Birgit; Schutte, R.; Friedrich, S.; Kistner, I.; Ott, Christian; Raff, U.; Veelken, Roland; Schmieder, Roland (Journal of Nephrology, 2015)
Hyperkalemia is a common and life-threatening complication frequently seen in patients with acute kidney injury, end-stage renal disease and chronic heart failure. Cardiac arrest and ventricular fibrillation are possible consequences. Biosensors are currently being developed to measure serum potassium under ambulatory conditions and trigger an alarm if the potassium concentration exceeds normal limits. Only few studies exist on the circadian rhythm of potassium; and its dependence on age and kidney function is less clear.Our observational monocentric exploratory study included 30 subjects of which 15 had impaired renal function (RF) (GFR <60 ml/min/1.73 m(2)). Subjects were further categorized into three age groups: 18-39 years (N normal RF = 5, N impaired RF = 4), 40-59 years (N normal RF = 5, N impaired RF = 6), 60-80 years (N normal RF = 5, N impaired RF = 5). Serum potassium levels were measured every 2 h during a 24 h period and repeated once after 2, 4, or 6 days.In the 15 subjects with normal RF, the lowest mean potassium level (3.96 ± 0.14 mmol/l) was observed at 9 p.m. and the greatest (4.23 ± 0.23 mmol/l) at 1 p.m. In patients with impaired RF the lowest mean potassium level (4.20 ± 0.32 mmol/l) was observed at 9 p.m. and the highest (4.57 ± 0.46 mmol/l) at 3 p.m. The range between the mean of minimum and maximum was greater in patients with impaired RF (0.71 ± 0.45 mmol/l) than in subjects with normal RF (0.53 ± 0.14 mmol/l) [p < 0.001]. No difference in the circadian rhythm was found between the first and second examination.Our results indicate that patients with normal and impaired RF have comparable circadian patterns of serum potassium concentrations, but higher fluctuations in patients with impaired RF. These results have clinical relevance for developing an automatic biosensor to measure the potassium concentration in blood under ambulatory conditions in patients at high risk for potassium fluctuations.
EVALuna2:3700